Field notes contributed by Bill F. Huser, fall 1987 - Huser, Bill F.et al (1987)
Fall report of birds found in northwest Iowa contributed by Bill F. Huser. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1987. Epson - sheet feed/flatbed